2023
DOI: 10.3389/fneur.2023.1155269
|View full text |Cite
|
Sign up to set email alerts
|

Intra-arterial tenecteplase is safe and may improve the first-pass recanalization for acute ischemic stroke with large-artery atherosclerosis: the BRETIS-TNK trial

Abstract: Background and purposeThe first-pass recanalization of endovascular treatment (EVT) is closely correlated with clinical outcome of patients with large vessel occlusion (LVO) stroke. The aim of the study was to explore whether intra-arterial tenecteplase (TNK) during the first pass of EVT can increase first-pass successful reperfusion and improve the neurological outcome in AIS-LVO patients.Materials and methodsThe BRETIS-TNK trial (ClinicalTrials.gov Identifier: NCT04202458) was a prospective, single-arm, sing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 45 publications
0
6
1
Order By: Relevance
“…Distal emboli occurred in 19.3% of MCA patients in our study, which was higher than that reported in previous studies 34 . It is noteworthy that secondary MeVO had poorer outcomes compared with LVO, 13 suggesting the need for more effective EVT methods to achieve complete recanalization, such as intra‐arterial thrombolysis during EVT 35,36 …”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…Distal emboli occurred in 19.3% of MCA patients in our study, which was higher than that reported in previous studies 34 . It is noteworthy that secondary MeVO had poorer outcomes compared with LVO, 13 suggesting the need for more effective EVT methods to achieve complete recanalization, such as intra‐arterial thrombolysis during EVT 35,36 …”
Section: Discussioncontrasting
confidence: 57%
“…34 It is noteworthy that secondary MeVO had poorer outcomes compared with LVO, 13 suggesting the need for more effective EVT methods to achieve complete recanalization, such as intra-arterial thrombolysis during EVT. 35,36 The presence of LMC varied by the location of arterial occlusion and was associated with good outcomes. [37][38][39] In this study, the proportion of LMC in patients with primary MeVO was significantly lower than that in patients with secondary MeVO (23% vs. 45%).…”
Section: Discussionmentioning
confidence: 99%
“…They hypothesized that immediate thrombolytic agent after MT would be important to reduce the risk of secondary MT and associated microembolization and endothelial injury. 71 Functional independence between treatment and control groups was not statistically significant. Here, multiple groups have attempted to treat only one of the 3 potential mechanisms of no-reflow.…”
Section: Discussionmentioning
confidence: 87%
“…Specifically, they found that patients treated with adjunct alteplase were significantly more likely to have an mRS score of 0 or 1 at 90 days compared with their control group. 70 Zhao et al 71 followed a similar paradigm but instead delivered intraarterial tenecteplase immediately following first-attempt MT. They hypothesized that immediate thrombolytic agent after MT would be important to reduce the risk of secondary MT and associated microembolization and endothelial injury.…”
Section: Discussionmentioning
confidence: 99%
“…The hypothesis was supported by our recent BRETIS-TNK study, which was a prospective, single-arm, single-centre study, indicating that intra-arterial TNK administration as an adjunct to mechanical thrombectomy seemed safe and feasible, with the potential to increase first-pass reperfusion rates (53.8% vs 36.0%) and good clinical outcome (50% vs 34.6%), compared with historical control patients. 13 Based on these pilot results, we designed this trial to determine the efficacy and safety of intra-arterial TNK administration during EVT in AIS-LVO patients.…”
Section: Introduction and Rationalementioning
confidence: 99%